Isolated cleft palate in mice with a targeted mutation of the LIM homeobox gene Lhx8 - Zhao, Yangu (The National Academy of Sciences, 1999)
Formation of the mammalian secondary palate is a highly regulated and complex process whose impairment often results in cleft palate, a common birth defect in both humans and animals. Loss-of-function analysis has linked a growing number of genes to this process. Here we report that Lhx8, a recently identified LIM homeobox gene, is expressed in the mesenchyme of the mouse palatal structures throughout their development. To test the function of Lhx8 in vivo, we generated a mutant mouse with a targeted deletion of the Lhx8 gene. Our analysis of the mutant animals revealed a crucial role for Lhx8 in palatogenesis. In Lhx8 homozygous mutant embryos, the bilateral primordial palatal shelves formed and elevated normally, but they often failed to make contact and to fuse properly, resulting in a cleft secondary palate. Because development of other craniofacial structures appeared normal, the impaired palatal formation in Lhx8-mutant mice was most likely caused by an intrinsic primary defect in the mesenchyme of the palatal shelves. The cleft palate phenotype observed in Lhx8-mutant mice suggests that Lhx8 is a candidate gene for the isolated nonsyndromic form of cleft palate in humans.